Structural Basis of the Interaction of Cyclin-Dependent Kinase 2 with Roscovitine and Its Analogues Having Bioisosteric Central Heterocycles - Nekardová, Michaela; Vymětalová, Ladislava; Khirsariya, Prashant; Kováčová, Silvia; Hylsová, Michaela; Jorda, Radek; Kryštof, Vladimír; Fanfrlík, Jindřich; Hobza, Pavel; Paruch, Kamil (Chemphyschem, 2017)
The structural basis for the interaction of roscovitine and analogues containing 13 different bioisosteric central heterocycles with the enzyme cyclin-dependent kinase 2 (CDK2) is elucidated. Although all the central scaffolds are very similar to the purine core of roscovitine, the experimentally determined IC50 values of the inhibitors span three orders of magnitude. By using an extensive computational chemistry approach, the affinities of the inhibitors to CDK2 are determined as calculated binding scores of complexes of the inhibitors with the protein. The interactions of the inhibitors with CDK2 are computationally described by using a hybrid quantum mechanics/semi-empirical quantum mechanics method (QM/SQM), which combines the DFT-D method for the QM part and the PM6-D3H4X method for the SQM part. The solvent effect is described by the COSMO implicit solvation model at the SQM level for the whole system. The contributions of the scaffolds and the individual substituents, quantified and evaluated in relation to conformations of optimized protein-inhibitor complexes, are found not to be simply additive. The inhibitory activity of the selected candidates, including two newly prepared compounds, is tested against CDK2. The results of the calculations are in close agreement with the experimental data.
Keywords: termodynamika; statická elektřina; Models, Molecular; roskovitin; Protein Kinase Inhibitors; Quantum Theory; kvantová teorie; krystalografie rentgenová; Static Electricity; computational chemistry; Roscovitine; scaffold hopping; protein-inhibitor interactions; Crystallography, X-Ray; heterocyklické sloučeniny; cyklin-dependentní kinasa 2; Heterocyclic Compounds; Thermodynamics; molekulární modely; purine bioisosteres; Purines; puriny; enzymes; molekulární struktura; inhibitory proteinkinas; Molecular Structure; Cyclin-Dependent Kinase 2